Gemeindefinanzreform. Hintergründe, Defizite, Alternativen. - Fuest, Clemens; Thöne, Michael (My University, 2005)
In kurzem Abstand sind in den Jahren 2000 und 2003 große politische Initiativen gescheitert, die wichtigsten deutschen Gemeindesteuern, die Grund und die Gewerbesteuer, zu reformieren. Die Studie fasst die diskutierten Reformmodelle zusammen und verweist auf die fortbestehende Notwendigkeit einer Reform der Gemeindesteuern. Die Defizite und Lücken der bisherigen Reformbemühungen werden analysiert und Alternativen entwickelt. Dabei werden besonders die bislang unbeachteten Vorteile der simultanen Reform von Gewerbe- und Grundsteuer gezeigt, die den meisten Gemeinden deutlich höhere Flexibilität eröffnet, reformbedingte Umverteilungseffekte abzufedern.

Within a few years, two major political initiatives to reform the most important German local taxes failed successively, in 2000 the reform of the real estate tax, in 2003 the reform of the trade tax (a special local business tax). The report offers a short survey of the reform discussion and the tax models discussed. With a view to the still pressing need for reform, we analyse the deficits and loopholes of the hitherto discussion and elaborate alternatives. Especially, we illustrate the benefits of a simultaneous reform of both local taxes: Mainly, local authorities gain flexibility to cushion unwanted redistributive effects of reform.
Local tax reform in germany.
Keywords: Finanzwesen; Gemeindefinanzreform; Öffentliche Einnahmen; Steuerpolitik; Gemeindesteuer; Gewerbesteuer; Grundsteuer; Reformmodell